2008
DOI: 10.1007/s00467-008-0796-z
|View full text |Cite
|
Sign up to set email alerts
|

Atypical presentation of distal renal tubular acidosis in two siblings

Abstract: Primary distal renal tubular acidosis (dRTA) is an inherited disease characterized by the inability of the distal tubule to lower urine pH <5.50 during systemic acidosis. We report two male siblings who presented with severe hyperchloremic metabolic acidosis, high urinary pH, nephrocalcinosis, growth retardation, sensorineural hearing loss, and hypokalemic paralysis. Laboratory investigations revealed proximal tubular dysfunction (low molecular weight proteinuria, generalized hyperaminoaciduria, hypophosphatem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 19 publications
2
23
0
1
Order By: Relevance
“…Renal proximal tubular dysfunction in untreated patients with dRTA has also been reported previously [1,2]. Although the precise pathogenic mechanism underlying development of this condition remains unclear, it has been suggested that hypokalemic nephropathy and defective V-ATPase resulting in impaired endosomal acidification may be involved [1,2].…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Renal proximal tubular dysfunction in untreated patients with dRTA has also been reported previously [1,2]. Although the precise pathogenic mechanism underlying development of this condition remains unclear, it has been suggested that hypokalemic nephropathy and defective V-ATPase resulting in impaired endosomal acidification may be involved [1,2].…”
mentioning
confidence: 77%
“…Although the precise pathogenic mechanism underlying development of this condition remains unclear, it has been suggested that hypokalemic nephropathy and defective V-ATPase resulting in impaired endosomal acidification may be involved [1,2]. However, because the B1 subunit of VATPase is not expressed in renal proximal tubular cells, defective V-ATPase is unlikely to cause renal proximal tubular dysfunction in dRTA patients with the ATPV1B1 mutation [2].…”
mentioning
confidence: 99%
“…These proximal tubular abnormalities were transitory and resolved with alkali therapy. Transitory proximal renal tubular dysfunction may be associated with distal RTA [2][3][4].…”
Section: Distal (Type I) Renal Tubular Acidosis (Rta)mentioning
confidence: 98%
“…However, following oral alkali therapy, all these abnormalities normalized. Watanabe [2] and our group [3] have previously described transitory proximal tubular dysfunction in children with distal RTA. The most likely mechanism for proximal tubular dysfunction is long-lasting hypokalemia.…”
Section: Commentarymentioning
confidence: 99%
“…Pertinent secondary references were also considered. Using this research technique, we were able to accumulate 9 cases (5 male and 4 female subjects, ranging in age between 4.0 and 46, median 21 years) of congenital renal tubular disorders complicated by hypokalemic rhabdomyolysis that have been published in peer-reviewed English-language scientific journals [11][12][13][14][15][16][17][18][19] between 1983 and 2008. One patient who was reported twice in the literature was considered only once [12,13].…”
Section: Systematic Review: Data Sourcesmentioning
confidence: 99%